Habitat deterioration for waterfowl in French fishponds: insight from trends in Mallard Anas platyrhynchos breeding success - Broyer, Joël (Wildfowl, 2020)
Declines in breeding success recently recorded for Pochard Aythya ferina nesting in French fishpond systems have raised questions about possible habitat change, which could be affecting other duck species as well. Here declines in measures of Mallard Anas platyrhynchos breeding success are described for four main fishpond regions (Dombes, Brenne, Forez and Sologne), which provide important waterfowl breeding habitats in France. Significant declines were recorded in the ratios of broods to the total number of Mallard pairs for Dombes, Brenne and Sologne, and in the brood sizes of one-week old families in Forez. No clear change was observed in duckling survival between 1–3 weeks of age. Annual breeding density of Mallard pairs varied unevenly across the study regions, decreasing in Sologne from 2004–2018 but increasing in Forez from 1992–2018. Such trends, similar to those previously recorded for the Pochard, support the hypothesis that habitat changes at French fishponds have affected the reproductive success of locally-breeding ducks. A possible influence of fish farming recession and the effect of Coypu Myocastor coypus feeding on nesting cover, are discussed.